Sinergitas Sains Dan Agama Dalam Kurikulum Pendidikan Islam Modern - Abrar, Kairul; Kustati, Martin; Sepriyanti, Nana; Reflianto, Reflianto; Amris, Firda Khairati (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
This research focuses on the importance of integration between science and religion in the modern Islamic Education curriculum. In an increasingly advanced and dynamic educational context, there is often a separation between science and religious values, even though both can enrich each other. The purpose of this study is to analyze how the synergy between science and religion can be applied in the Islamic Education curriculum as well as its impact on student character building. The method used in this research is a qualitative approach with literature study and observation of the Islamic Education curriculum in several educational institutions. The results showed that the integration of science and religion in the curriculum can form a generation that is not only intellectually superior, but also has a strong moral and spiritual foundation. In conclusion, the application of synergy between science and religion in the Islamic Education curriculum can improve the quality of education and form a balanced person between the mind, heart, and charity.